New insight of Arctic cloud parameterization from regional climate model simulations, satellite‐based, and drifting station data. Issue 10 (23rd May 2016) - Klaus, D.; Dethloff, K.; Dorn, W.; Rinke, A.; Wu, D. L.
Abstract: Cloud observations from the CloudSat and CALIPSO satellites helped to explain the reduced total cloud cover ( C tot ) in the atmospheric regional climate model HIRHAM5 with modified cloud physics. Arctic climate conditions are found to be better reproduced with (1) a more efficient Bergeron‐Findeisen process and (2) a more generalized subgrid‐scale variability of total water content. As a result, the annual cycle of C tot is improved over sea ice, associated with an almost 14% smaller area average than in the control simulation. The modified cloud scheme reduces the C tot bias with respect to the satellite observations. Except for autumn, the cloud reduction over sea ice improves low‐level temperature profiles compared to drifting station data. The HIRHAM5 sensitivity study highlights the need for improving accuracy of low‐level (<700 m) cloud observations, as these clouds exert a strong impact on the near‐surface climate. Key Points: Stratiform cloud parameterization is improved based on satellite data Cloud reduction is accompanied by smaller low‐level temperature bias over ice Derived parameterization may reduce uncertainties in Arctic climate projections